1996
DOI: 10.1177/0306624x96404006
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Parental Characteristics of Youthful Sexual Offenders

Abstract: This study, employing meta-analysis, investigates 20 years (1973-1993) of empirical data involving demographic and parental correlates of youthful sexual offenders. Three offender subtypes, pedophilic, sexual assault, and mixed offense youth, are identified. Pedophilic youth are described as being principally Caucasian, living in foster care, and having an education of < sixth grade. They tend to be from lower to mid socioeconomic status (SES) maladaptive families. Mothers of these youth have been physicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 28 publications
4
43
2
Order By: Relevance
“…However, in agreement with Hunter et al (2000) and Hendriks and Bijleveld (2004), we found that majority ethnicity was somewhat overrepresented among ASOs with child victims and underrepresented among ASOs with adolescent/adult victims. This is in contrast with Graves et al (1996) Child ASOs were more likely to have male victims than peer ASOs. This finding confirmed results previously presented by Hunter et al (2000) and Hendriks and Bijleveld (2004).…”
Section: Child Vs Peer Offenderscontrasting
confidence: 58%
See 1 more Smart Citation
“…However, in agreement with Hunter et al (2000) and Hendriks and Bijleveld (2004), we found that majority ethnicity was somewhat overrepresented among ASOs with child victims and underrepresented among ASOs with adolescent/adult victims. This is in contrast with Graves et al (1996) Child ASOs were more likely to have male victims than peer ASOs. This finding confirmed results previously presented by Hunter et al (2000) and Hendriks and Bijleveld (2004).…”
Section: Child Vs Peer Offenderscontrasting
confidence: 58%
“…Finally, Graves, Openshaw, Ascione, and Ericksen (1996) reported on a systematic review of the published ASO literature from 1973 to 1993. They identified child offenders, peer offenders, and "mixed" offenders as the three most clearly distinguishable offender categories in clinical samples.…”
Section: Child Vs Peer Offendersmentioning
confidence: 99%
“…With respect to demographic characteristics, the finding that rates of single-parent homes were the same for the families of adolescent CSA perpetrators and both normal and clinical control is not consistent with findings from other studies where higher rates of single parent homes were found among adolescent CSA perpetrators (Kaplan et al, 1990;Graves et al, 1996;O'Reilly et al, 1998;Hsu and Starzynski, 1990;Browne and Falshaw, 1998;Manocha and Mezey, 1998;Gray et al, 1999). It is, however, consistent with Bagley's (1992) results where it was found that the majority of his sample of adolescent sexual offenders came from intact families.…”
Section: Comparison With Other Studiescontrasting
confidence: 59%
“…The heterogeneity of the target group profiled in this study may have concealed important differences between different subgroups of sexually abusive adolescents. For example, Graves, Openshaw, Ascoine and Ericksen (1996) in a meta-analysis identified three distinct subgroups of adolescent offenders: the paedophilic offender, the sexual assault offender, and the mixed-offence offender. They found that paedophilic and sexually assaultive youths came from families in which the structure was judged to be chaotic-rigid, or disengaged-enmeshed.…”
Section: Implications For Researchmentioning
confidence: 99%
“…For example, they show more behaviour problems than normal controls but not incarcerated controls; they have difficulties with making and maintaining friendships and establishing empathy with others; they have problems with impulse control, anger management and assertiveness; and they come from families characterized by a variety of problems (Graves, Openshaw, Ascoine, & Ericksen, 1996;Hastings, Anderson, & Hemphill, 1997;James & O'Neil, 1996;Monto, Zgourides, & Harris, 1998;Monto, Zgourides , Harris, & Wilson, 1994;Vizard, Monck, & Misch, 1995). Despite the burgeoning international literature in this area, few studies have been conducted on Irish adolescent sexual abusers (Carr, 1999a(Carr, ,1999bO'Reilly & Carr, 1998) and non-adjudicated abusers.…”
Section: Introductionmentioning
confidence: 99%